Do large registered investment funds undermine shareholder activism? Evidence from hedge fund proposals - Loureiro, Gilberto; Mendonça, Cesar (Journal of Banking & Finance, 2024)
We examine the voting behavior of Registered Investment Funds (Mutual Funds, ETFs and Close-end Funds) on Hedge Funds proposals, a common vehicle of value-driven shareholder activism. We compare the support rates of Registered Funds versus other voting shareholders on different types of proposals set up for voting at shareholders meetings and explore fund-level characteristics that may explain the variation in support rates. Our results show that Registered Funds support rates on Hedge Fund proposals vary depending on the proposal category. In general, the support rates of Registered Funds are about 4 percentage points lower compared to other investors. However, that difference rises to 10 p.p. for proposals that are more confrontational to the incumbent management of the target company. Interestingly, the average lower support rates of Registered Funds are driven by the ten largest funds. On the contrary, Registered Funds from smaller parent groups tend to be more supportive of Hedge Fund activism. We document a 18 p.p. reduction in the probability of favorable votes on Hedge Fund proposals by the largest Registered Funds compared to smaller funds. Our results suggest that the growing ownership in public companies by large Registered Funds reduces the overall support of shareholder activism through Hedge Fund proposals.